Kinerja Keuangan dan Harga Saham pada Perusahaan Konsumen Non-Siklus di Bursa Efek Indonesia Periode 2022–2024 - Rania Syahla Qumaira; Amelia Setiawan; Hamfri Djajadikerta (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Stock price is one of the main indicators in the capital market that reflects investors perceptions of a company's value and performance. Although the Non-Cyclical Consumer sector is considered relatively stable, stock prices in this sector may still fluctuate due to changes in financial performance and investors responses to published information. This research aims to examine the influence of Return on Equity (ROE), Debt-to-Equity Ratio (DER), and Earnings Per Share (EPS) on the stock price of companies in the Non-Cyclical Consumer sector listed on  Indonesia Stock Exchange during 2022–2024 period. This research employs a quantitativ approach with an associativ research design. Data use consists of second data in  form of audited annual financial statements and stock prices as of the date the financial statements’ publication. The sample was select using purposive sampling, comprising 12 companies with 36 observations. The analysis technique employed multiple linear regresion at  5% significance level. The results imply that ROE has positive relationship on stock prices, DER has negative relationship, while EPS is proven to have positive and significant effects. Simultaneously, ROE, DER, and EPS have significants relationship on stock prices with an Adjusted R-Square value of 66.78%. The findings indicate that Earnings Per Share (EPS) is the most considered variable by investors in evaluating Non-Cyclical Consumer sector companies when making investment decisions.